2017
DOI: 10.7554/elife.22799
|View full text |Cite
|
Sign up to set email alerts
|

DNA-mediated association of two histone-bound complexes of yeast Chromatin Assembly Factor-1 (CAF-1) drives tetrasome assembly in the wake of DNA replication

Abstract: Nucleosome assembly in the wake of DNA replication is a key process that regulates cell identity and survival. Chromatin assembly factor 1 (CAF-1) is a H3-H4 histone chaperone that associates with the replisome and orchestrates chromatin assembly following DNA synthesis. Little is known about the mechanism and structure of this key complex. Here we investigate the CAF-1•H3-H4 binding mode and the mechanism of nucleosome assembly. We show that yeast CAF-1 binding to a H3-H4 dimer activates the Cac1 winged helix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
107
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(134 citation statements)
references
References 62 publications
13
107
1
Order By: Relevance
“…3c). This was confirmed when we measured nucleosome assembly activity of the tCAF-1 subcomplexes in a quantitative nucleosome assembly (NAQ) assay37 (Fig. 3d).…”
Section: Resultssupporting
confidence: 65%
“…3c). This was confirmed when we measured nucleosome assembly activity of the tCAF-1 subcomplexes in a quantitative nucleosome assembly (NAQ) assay37 (Fig. 3d).…”
Section: Resultssupporting
confidence: 65%
“…CAF-1 is a heterotrimeric chaperone composed of p150, p60 and RbAp48 (also known as p48) subunits, also known as Cac1, Cac2, and Cac3 in yeast, respectively. Early studies suggested that human CAF-1 binds to and deposits H3.1/H4 dimers in vivo [23], however more recent evidence suggests that yeast CAF-1 forms tetramers of two H3/H4 dimers and deposits the tetrameric form onto DNA [154,155], though the mechanisms of tetramerization in the human protein remains an active area of research. The Cac1/p150 subunit is largely disordered and contains a large acidic stretch (the glutamate/aspartate or ED domain) in the middle of the protein sequence (Figure 3).…”
Section: Introductionmentioning
confidence: 99%
“…Data normalization to a loading control DNA allows us to compare and accurately quantify the amount of nucleosomes formed in different samples. The NAQ assay has been successfully used to measure the activity of the chromatin assembly factor 1 (CAF-1) in vitro (Mattiroli et al ., 2017a and 2017b), and has the potential to reveal the differential contribution of histone chaperones to nucleosome assembly in cells. This will pave the way for the complete understanding of their functional roles in nucleosome dynamics.…”
Section: Introductionmentioning
confidence: 99%